Novel Mechanism of Steroid Action in Skin through Glucocorticoid Receptor Monomers - Radoja, Nadezda (American Society for Microbiology, 2000)
Glucocorticoids (GCs), important regulators of epidermal growth, differentiation, and homeostasis, are used extensively in the treatment of skin diseases. Using keratin gene expression as a paradigm of epidermal physiology and pathology, we have developed a model system to study the molecular mechanism of GCs action in skin. Here we describe a novel mechanism of suppression of transcription by the glucocorticoid receptor (GR) that represents an example of customizing a device for transcriptional regulation to target a specific group of genes within the target tissue, in our case, epidermis. We have shown that GCs repress the expression of the basal-cell-specific keratins K5 and K14 and disease-associated keratins K6, K16, and K17 but not the differentiation-specific keratins K3 and K10 or the simple epithelium-specific keratins K8, K18, and K19. We have identified the negative recognition elements (nGREs) in all five regulated keratin gene promoters. Detailed footprinting revealed that the function of nGREs is to instruct the GR to bind as four monomers. Furthermore, using cotransfection and antisense technology we have found that, unlike SRC-1 and GRIP-1, which are not involved in the GR complex that suppresses keratin genes, histone acetyltransferase and CBP are. In addition, we have found that GR, independently from GREs, blocks the induction of keratin gene expression by AP1. We conclude that GR suppresses keratin gene expression through two independent mechanisms: directly, through interactions of keratin nGREs with four GR monomers, as well as indirectly, by blocking the AP1 induction of keratin gene expression.